2020
DOI: 10.1002/app.49902
|View full text |Cite
|
Sign up to set email alerts
|

N‐phosphorylated Iminophosphoranes based on 9,10‐Dihydro‐9‐oxa‐10‐phosphaphenanthrene‐10‐oxide and their flame‐retardant behavior in epoxy resins

Abstract: Two novel N-phosphorylated iminophosphoranes based on 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) were evaluated as flame retardant (FR) additives. They were incorporated in two different epoxy resin systems (EP) based on diglycidyl ether of bisphenol A (DGEBA) and a novolac glycidyl ether (DEN438) both cured with dicyandiamide/fenuron (D/F). Decomposition temperatures and char yields of the cured EP were evaluated and compared to the corresponding neat EP as well as to structurally related compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The first of these halogenated and phosphorus chemicals are no longer in use today, but the underlying chemical concepts are well understood and in continued use owing to their proven effectiveness over the years. The current flame retardants are products of decades of research and development and they have been tailor-made for use in certain polymers under specific circumstances [ 67 , 68 , 69 , 70 , 71 ]. Flame retardants are usually categorized into two classes: Additive (non-reactive) and reactive types, as shown in Table 2 ; the additive type is further divided into organic and inorganic flame retardants [ 72 , 73 ].…”
Section: Types Of Flame Retardantsmentioning
confidence: 99%
“…The first of these halogenated and phosphorus chemicals are no longer in use today, but the underlying chemical concepts are well understood and in continued use owing to their proven effectiveness over the years. The current flame retardants are products of decades of research and development and they have been tailor-made for use in certain polymers under specific circumstances [ 67 , 68 , 69 , 70 , 71 ]. Flame retardants are usually categorized into two classes: Additive (non-reactive) and reactive types, as shown in Table 2 ; the additive type is further divided into organic and inorganic flame retardants [ 72 , 73 ].…”
Section: Types Of Flame Retardantsmentioning
confidence: 99%
“…In recent years, petroleum‐based plastics have been increasingly used in everyday life due to their light weight, excellent chemical resistance, and ease of processing 1–3 . However, the common petrochemical‐based plastics are unsustainable materials and do not degrade, which is contrary to the sustainable development that we now advocate 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…A typical phosphorus‐containing compound, 9,10‐dihydro‐9‐oxa‐10‐phosphaphenanthrene 10‐oxide (DOPO) and its based derivatives, can exert an excellent flame retardancy in EP 12 . For example, Manfred et al, synthesized DOPO derivatives with different chemical states of phosphorus and found the peak heat release rate of the flame retardant composites was reduced by over 50% with a relatively low phosphorus content, while the smoke release increased to some extent 13 . Netkueakul et al, studied the effect of DOPO and graphene nanoplatelets (GNP) in flame retardant epoxy resin (EP), and found the peak heat release rate of EP was dramatically decreased with an increase in the DOPO content, while the smoke production of EP/DOPO/GNP composites was suppressed in comparison with EP containing only DOPO as flame retardant 14 .…”
Section: Introductionmentioning
confidence: 99%